Development, Psychometric Testing, and Use of a Disaster Nursing Competency Scale in Iran: A Mixed Methods Study. (17th October 2022) - Aliakbari, Fatemeh; Aein, Fereshteh; Bahrami, Masoud; Arbon, Paul
Abstract: Nurses play an important role during disaster response and recovery. Few tools are available to assess the relative competence of nurses in disaster. This study aimed to develop, test, and evaluate a disaster nursing competency scale. This was an exploratory mixed methods study. In the qualitative phase, 35 Iranian nurses and managers with experience in disaster relief were asked about the skills they need to respond effectively to a disaster event. From the qualitative data, a 50-item questionnaire was developed. In the quantitative phase, exploratory factor analysis was conducted with 400 samples followed by a test-retest reliability assessment with 30 nurses. The developed and validated instrument was applied to 200 nurses in Iran to assess their competency. From content analysis of the qualitative data, 5 main themes emerged. In the quantitative phase, exploratory factor analysis loaded 50 items into 4 domains named management, legal and ethical, specific personal, and technical competence. Use of the tool showed that nurses estimated their competence overall at 70.28%. Findings demonstrate the necessity for new domains in disaster nursing competencies; which may be applicable as a useful tool and guideline to improve nursing education and practice.